Molecular features of aggressive thyroid cancer - Elia, Giusy; Patrizio, Armando; Ragusa, Francesca; Paparo, Sabrina Rosaria; Mazzi, Valeria; Balestri, Eugenia; Botrini, Chiara; Rugani, Licia; Benvenga, Salvatore; Materazzi, Gabriele; Spinelli, Claudio; Antonelli, Alessandro; et al. (Frontiers in Oncology, 2022)
Poorly differentiated thyroid cancer (PDTC) and anaplastic thyroid cancer (ATC) have a worse prognosis with respect to well differentiated TC, and the loss of the capability of up-taking 131I is one of the main features characterizing aggressive TC. The knowledge of the genomic landscape of TC can help clinicians to discover the responsible alterations underlying more advance diseases and to address more tailored therapy. In fact, to date, the antiangiogenic multi-targeted kinase inhibitor (aaMKIs) sorafenib, lenvatinib, and cabozantinib, have been approved for the therapy of aggressive radioiodine (RAI)-resistant papillary TC (PTC) or follicular TC (FTC). Several other compounds, including immunotherapies, have been introduced and, in part, approved for the treatment of TC harboring specific mutations. For example, selpercatinib and pralsetinib inhibit mutant RET in medullary thyroid cancer but they can also block the RET fusion proteins-mediated signaling found in PTC. Entrectinib and larotrectinib, can be used in patients with progressive RAI-resistant TC harboring TRK fusion proteins. In addition FDA authorized the association of dabrafenib (BRAFV600E inhibitor) and trametinib (MEK inhibitor) for the treatment of BRAFV600E-mutated ATC. These drugs not only can limit the cancer spread, but in some circumstance they are able to induce the re-differentiation of aggressive tumors, which can be again submitted to new attempts of RAI therapy. In this review we explore the current knowledge on the genetic landscape of TC and its implication on the development of new precise therapeutic strategies.